Operational Risk Assessment of a 150,000 DWT Single Buoy Mooring - Muhammad Bayu Abisatya; Silvianita sil; Daniel Mohammad Rosyid (International Journal of Offshore and Coastal Engineering, 2026)
Single Buoy Mooring (SBM) is a critical offshore facility used for tanker berthing and fluid transfer in oil and gas distribution systems, where complex interactions between vessels, mooring components, mechanical equipment, and dynamic marine environments generate significant operational risks. This study assesses the operational risks of a 150,000 DWT SBM system using a semi-quantitative Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach integrated with expert judgment. Hazard identification was conducted across all operational stages, including approaching, mooring, fluid transfer, and departing. Risk assessment was performed by evaluating the Likelihood of Failure (LoF) and the Consequence of Failure (CoF), with CoF assessed across safety, environmental, and asset/operational dimensions. Risk ranking employed a worst-case approach by selecting the maximum risk value among the three dimensions. The results indicate that hazards related to mooring chain integrity, pretension control, and swivel sealing systems present high to very high-risk levels. Further analysis using Bow-Tie Analysis highlights escalation pathways and the effectiveness of existing control barriers. The study demonstrates that the integrated HIRARC and Bow-Tie framework provides a practical basis for prioritizing operational risk controls in large-capacity SBM systems under limited historical failure data.